Continuing medical education for general practitioners: a practice format - VanNieuwenborg, Lena (Postgrad Med J, 2016)
INTRODUCTION: Our current knowledge-based society and the many actualisations within the medical profession require a great responsibility of physicians to continuously develop and refine their skills. In this article, we reflect on some recent findings in the field of continuing education for professional doctors (continuing medical education, CME). Second, we describe the development of a CME from the Academic Center for General Practice (ACHG) of the KU Leuven. METHODS: First, we performed a literature study and we used unpublished data of a need assessment performed (2013) in a selected group of general practitioners. Second, we describe the development of a proposal to establish a CME programme for general practitioners. RESULTS: CME should go beyond the sheer acquisition of knowledge, and also seek changes in practice, attitudes and behaviours of physicians. The continuing education offerings are subject to the goals of the organising institution, but even more to the needs and desires of the end user. CONCLUSIONS: Integrated education is crucial to meet the conditions for efficient and effective continuing education. The ACHG KU Leuven decided to offer a postgraduate programme consisting of a combination of teaching methods: online courses (self-study), contact courses (traditional method) and a materials database.